Preparation method and application of high-toughness bamboo holocellulose nanofiber
By using a low-melt solvent prepared by D-xylose and choline chloride to treat bamboo cellulose, combined with solid-liquid separation and ultrasonic crushing technology, high-strength and tough bamboo cellulose nanofibers were prepared, solving the problems of single preparation methods and high treatment energy consumption in the prior art, and achieving the preparation of high-performance bamboo nanocellulose films.
Patent Information
- Application Number
- CN202510290700.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-12
AI Technical Summary
The existing nano-integrated cellulose preparation methods have problems such as single preparation methods, high energy consumption, long time consumption and insufficient research on subsequent application methods, and cannot fully meet the actual production needs.
D-xylose and choline chloride are used to prepare eutectic solvents to treat bamboo cellulose. High-strength and tough bamboo cellulose nanofibers are prepared through solid-liquid separation and ultrasonic crushing technology to ensure the protection of hemicellulose content.
The preparation of high-strength and toughness bamboo cellulose nanofibers was realized. The resulting bamboo nanocellulose film has the advantages of high light transmittance, high tensile stress and high toughness, which solved the problems of low hemicellulose content and high processing energy consumption.
Smart Images

Figure CN119824705A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cellulose processing, and in particular relates to a preparation method of high-strength and toughness bamboo holocellulose nanofibers and applications thereof. Background Art
[0002] In recent years, with the great development of the world's industrial level, the problems of environmental pollution and the depletion of non-renewable resources have become increasingly severe. High-performance new green materials have received widespread attention from researchers at home and abroad. Lignocellulose is mainly composed of cellulose, hemicellulose and lignin. It has the advantages of low price, wide source, high biocompatibility, green and pollution-free. It is expected to replace non-renewable resources and is a very promising renewable resource. Cellulose is the most abundant natural polymer on earth and is widely used as a raw material for functional applications. Nanocellulose is a slender fiber or crystal with a nanoscale (1-100nm) obtained by chemical, mechanical and other pretreatment methods of lignocellulose raw materials. It can be widely used in the preparation of new green materials and has excellent properties in mechanical properties, optical properties, electrical properties, etc. In the process of preparing nanocellulose, hemicellulose is retained to obtain nanoholocellulose (HCNFs). Nanoholocellulose retains the binding state of some natural components in the plant body to form a unique "core-shell" structure. Compared with nanocellulose, nanoholocellulose containing hemicellulose often has higher mechanical properties, optical transmittance and thermal stability, and has obvious performance advantages.
[0003] The main reported methods for preparing nano-holocellulose are as follows: CN 202410172854.1 discloses a method for preparing bamboo holocellulose of different forms by ball milling-assisted enzyme method. In this method, bamboo pulp is ball milled, and then deionized water, buffer, enzyme and tetracycline are added for enzymatic hydrolysis. After the enzymatic hydrolysis is completed, bamboo pulp fibers are boiled, inactivated, washed and dried to obtain bamboo pulp fibers, and then the bamboo pulp fibers are ultrasonically crushed and dispersed to obtain bamboo holocellulose suspension. Nanocellulose with an aspect ratio of 1.2 to 4.5 nm is prepared by changing the ball milling time and the amount of enzyme added, and the concentration of nanocellulose is greater than 160 mg / L. Yang et al. [Yang X, Berthold F, Berglund L A. Preserving cellulose structure: delignified wood fibers for paper structures of high strength and transparency [J]. Biomacromolecules, 2018, 19 (7): 3020-3029.] used spruce wood delignified by peracetic acid as raw material and used a kitchen blender to mechanically nano-treat it to prepare HCNFs with a smaller diameter. Because it was not subjected to additional chemical treatment, the hemicellulose on the individual fibers in the cell wall of the wood plant was largely retained. The resulting HCNFs had a diameter of less than 5 nm and a length of about 2.5 μm. Ding et al. [Ding Q, Rao J, Lv Z, et al. Efficient preparation of holocellulose nanofibers and their reinforcement potential [J]. Cellulose, 2022, 29 (15): 8229-8242.] used a simple mechanical grinding method to prepare HCNFs from different types of lignocellulosic biomass such as wheat straw, bamboo, hardwood, and softwood. The resulting HCNFs retained a high hemicellulose content and a complete "core-shell" structure. Galland et al. [Galland S, Berthold F, Prakobna K, et al. Holocellulose nanofibers of high molar mass and small diameter for high-strength nanopaper [J]. Biomacromolecules, 2015, 16 (8): 2427-2435.] microfluidized pretreatment of poplar and spruce wood from which lignin had been removed, and successfully prepared HCNFs with a hemicellulose content of 24%.Hemicellulose plays a role in transferring stress between fibers, greatly improving the stretchability of HCNFs nanofilms.
[0004] It can be seen that the existing preparation methods of nano-holocellulose often have problems such as single preparation method, high processing energy consumption, long processing time and insufficient research on subsequent application methods, and cannot fully meet the needs of use in actual production. Summary of the invention
[0005] The first purpose of the present invention is to provide a method for preparing high-strength and toughness bamboo holocellulose nanofibers, which has a simple process, mild reaction conditions, is environmentally friendly, and is easy to operate.
[0006] The second object of the present invention is to disclose a high-strength and toughness bamboo holocellulose nanofiber, which is evenly dispersed and can effectively protect the hemicellulose content in the nano holocellulose.
[0007] The third purpose of the present invention is to disclose the use of high-strength and toughness bamboo holocellulose nanofibers in the preparation of bamboo nano holocellulose films, and the obtained bamboo nano holocellulose films have good mechanical properties.
[0008] In order to solve the above problems, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing high-strength and toughness bamboo holocellulose nanofibers, comprising first preparing a low eutectic solvent using D-xylose and choline chloride, treating the bamboo holocellulose using the low eutectic solvent, then performing solid-liquid separation, dispersing the solid, and obtaining the bamboo holocellulose nanofibers by ultrasonic treatment;
[0010] The hemicellulose content in the bamboo holocellulose nanofibers is not less than 19%; the cellulose content in the bamboo holocellulose nanofibers is not less than 68%.
[0011] Furthermore, the molar ratio of D-xylose to choline chloride is 1:2.
[0012] Furthermore, the solid-liquid mass ratio of the bamboo holocellulose to the low eutectic solvent is 1g:20g.
[0013] Furthermore, during the treatment of the bamboo holocellulose with the low eutectic solvent, the mixture was stirred and mixed evenly with a glass rod, and the mixture was heated in an oil bath at 100-130° C. for 120 min.
[0014] Furthermore, the oil bath heating temperature is 110°C.
[0015] Furthermore, the method for dispersing the solid is as follows: cooling the bamboo holocellulose residue after solid-liquid separation to room temperature, washing with deionized water and freeze-drying, and then re-dispersing the bamboo holocellulose residue in deionized water.
[0016] Furthermore, the ultrasonic treatment method is: the power of the cell disruptor used is 650W, the treatment time is 20min, and the ultrasonic treatment is paused for 5s every 5s.
[0017] Furthermore, the preparation method of any of the above-mentioned high-strength and toughness bamboo holocellulose nanofibers comprises the following steps:
[0018] (1) D-xylose and choline chloride were uniformly mixed in a molar ratio of 1:2 and magnetically stirred at 85°C for 30 min until a uniform transparent liquid appeared;
[0019] (2) 3 g of bamboo holocellulose powder and 60 g of DES were mixed, and the mixture was heated in an oil bath at 100-130 °C for 120 min, cooled to room temperature, and thoroughly washed with deionized water. After washing, the powder residue was freeze-dried;
[0020] (3) The power of the cell disruptor used was 650 W, and the processing time was 20 min. The bamboo holocellulose nanofibers were broken by ultrasonication for 5 s and then paused for 5 s, followed by rapid centrifugation to separate HCNF from solid residue.
[0021] Furthermore, any of the above methods can be used to prepare high-strength and tough bamboo holocellulose nanofibers.
[0022] Furthermore, the high-strength and toughness bamboo holocellulose nanofibers are used in the preparation of bamboo nano-holocellulose films, and the method is: the prepared bamboo holocellulose nanofibers are configured into a nano-holocellulose suspension with a mass fraction of 1%, and a film is prepared by a vacuum filtration method.
[0023] According to the interaction between hemicellulose and cellulose in bamboo cell walls and the mechanical support structure, the invention applies the improvement of plant mechanical strength to the field of nanofiber preparation, treats bamboo holocellulose with a choline chloride-xylose low eutectic solvent, separates the solid and liquid after the treatment, disperses the solid, obtains bamboo holocellulose nanofibers through simple ultrasonic crushing, and prepares high-strength bamboo nano holocellulose film. The conversion and utilization of bamboo nano holocellulose is realized, the problems of high processing energy consumption and low hemicellulose content in nanofibers are solved, and the utilization of all components of bamboo bioconversion is promoted to a certain extent.
[0024] Compared with the prior art, the advantages of the present invention are as follows:
[0025] 1) The present invention can not only effectively prepare nano-holocellulose with high hemicellulose content, but also the obtained bamboo nano-holocellulose film has the advantages of high light transmittance, high tensile stress and high toughness.
[0026] 2) The present invention not only effectively protects the hemicellulose content in the nano-holocellulose, but also achieves the enhancement of the mechanical properties of the nano-holocellulose film. The obtained bamboo nano-holocellulose has the advantages of uniform dispersion and the like.
[0027] 3) The present invention not only has many advantages such as simple process, mild reaction conditions, environmental friendliness, and easy operation, but also utilizes the decomposition product (xylose) of bamboo hemicellulose, which is beneficial to the full component utilization of bamboo lignocellulose raw materials in bioconversion. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is the atomic force microscope (AFM) image, Tyndall effect schematic diagram, and height distribution map of nano-holocellulose after pretreatment with a low eutectic solvent;
[0029] Figure 2 is the particle size distribution and zeta potential diagram of nano-holocellulose after pretreatment with a deep eutectic solvent;
[0030] Figure 3 It is a schematic diagram of the visible light transmittance of the nano-holocellulose film prepared in the present application, a tensile stress curve of the nano-cellulose film prepared by the traditional Tempo oxidation method, a comparison diagram of toughness and Young's modulus, and a comparison diagram of cell activity;
[0031] Figure 4 Schematic diagram of the preparation of different molar ratios of choline chloride / D-xylose. From left to right, the molar ratios of choline chloride:xylose are 1:1, 1:2, 1:3, 2:1, and 3:1, respectively. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.
[0033] The raw material bamboo holocellulose used in the following examples is a commercially available product, and its main components are: cellulose (about 56%), hemicellulose (about 25%), a small amount of lignin (about 6%), and other components (remaining). The raw material bamboo holocellulose can also be prepared by bleaching bamboo with sodium chlorite / acetic acid.
[0034] The characterization methods of the HCNF products prepared in the following examples are as follows:
[0035] AFM observation: The nanoholocellulose suspension was diluted 0.5% and dropped on a smooth mica sheet. After natural air drying, the nanofiber morphology was observed using an atomic force microscope to obtain the average length (nm), average width (nm) and aspect ratio.
[0036] Determination of crystallinity: The instrument used is X-ray diffractometer, crystallinity (%) = crystalline region peak area / (crystalline region peak area + amorphous region peak area)*100%.
[0037] Determination of glucan and xylan content: The U.S. Energy Laboratory's special wood fiber component determination method was used to determine the content of components in the hydrolyzate after sulfuric acid hydrolysis using ion chromatography;
[0038] Glucose content (%) = glucose content in hydrolyzate (g) / mass of original enzymatic hydrolysis material (g) * 100%;
[0039] Xylan content (%) = xylose content in hydrolyzate (g) / mass of original enzymatic hydrolysis material (g) * 100%.
[0040] Example 1
[0041] A method for preparing high-strength and toughness bamboo holocellulose nanofibers, comprising the following steps:
[0042] (1) Preparation of deep eutectic solvent (DES): D-xylose (D-xyl) and choline chloride (ChCl) were uniformly mixed in a molar ratio of 1:2 and magnetically stirred at 85 °C for 30 min until a uniform transparent liquid appeared;
[0043] (2) Pretreatment: Add 3 g of bamboo holocellulose powder and 60 g of DES into a glass conical bottle, stir and mix evenly with a glass rod, and heat the mixture in an oil bath at 100 °C for 120 min. After pretreatment, cool the mixture to room temperature, wash it thoroughly with deionized water, and freeze-dry the powder residue after washing;
[0044] (3) Preparation of HCNF: The powder residue after freeze-drying in step (2) was dispersed in water at a mass ratio of 1:20, and then ultrasonically disrupted to prepare bamboo holocellulose nanofibers; wherein the power of the cell disruptor used for ultrasonication was 650 W, the treatment time was 20 min, and the ultrasonication was paused for 5 s every 5 s. After the ultrasonic treatment, the sample was rapidly centrifuged to separate the supernatant and the solid residue. The supernatant finally obtained was the bamboo holocellulose nanofiber (HCNF) suspension, named CX-100.
[0045] Example 2
[0046] A method for preparing high-strength and toughness bamboo holocellulose nanofibers, comprising the following steps:
[0047] (1) Preparation of deep eutectic solvent (DES): D-xylose (D-xyl) and choline chloride (ChCl) were uniformly mixed in a molar ratio of 1:2 and magnetically stirred at 85 °C for 30 min until a uniform transparent liquid appeared;
[0048] (2) Pretreatment: Add 3 g of bamboo holocellulose powder and 60 g of DES into a glass conical bottle, stir and mix evenly with a glass rod, and heat the mixture in an oil bath at 110°C for 120 min. After pretreatment, cool the mixture to room temperature, wash it thoroughly with deionized water, and freeze-dry the powder residue after washing;
[0049] (3) Preparation of HCNF: The powder residue after freeze-drying in step (2) was dispersed in water at a mass ratio of 1:20, and then ultrasonically disrupted to prepare bamboo holocellulose nanofibers; wherein the power of the cell disruptor used for ultrasonication was 650 W, the treatment time was 20 min, and the ultrasonication was paused for 5 s every 5 s. After the ultrasonic treatment, the sample was rapidly centrifuged to separate the supernatant and the solid residue. The supernatant finally obtained was the bamboo holocellulose nanofiber (HCNF) suspension, named CX-110.
[0050] Example 3
[0051] A method for preparing high-strength and toughness bamboo holocellulose nanofibers, comprising the following steps:
[0052] (1) Preparation of deep eutectic solvent (DES): D-xylose (D-xyl) and choline chloride (ChCl) were uniformly mixed in a molar ratio of 1:2 and magnetically stirred at 85 °C for 30 min until a uniform transparent liquid appeared;
[0053] (2) Pretreatment: Add 3 g of bamboo holocellulose powder and 60 g of DES into a glass conical bottle, stir and mix evenly with a glass rod, and heat the mixture in an oil bath at 120 °C for 120 min. After pretreatment, cool the mixture to room temperature, wash it thoroughly with deionized water, and freeze-dry the powder residue after washing;
[0054] (3) Preparation of HCNF: The powder residue after freeze-drying in step (2) was dispersed in water at a mass ratio of 1:20, and then ultrasonically disrupted to prepare bamboo holocellulose nanofibers; wherein the power of the cell disruptor used for ultrasonication was 650 W, the treatment time was 20 min, and the ultrasonication was paused for 5 s every 5 s. After the ultrasonic treatment, the sample was rapidly centrifuged to separate the supernatant and the solid residue. The supernatant finally obtained was the bamboo holocellulose nanofiber (HCNF) suspension, named CX-120.
[0055] Example 4
[0056] A method for preparing high-strength and toughness bamboo holocellulose nanofibers, comprising the following steps:
[0057] (1) Preparation of deep eutectic solvent (DES): D-xylose (D-xyl) and choline chloride (ChCl) were uniformly mixed in a molar ratio of 1:2 and magnetically stirred at 85 °C for 30 min until a uniform transparent liquid appeared;
[0058] (2) Pretreatment: Add 3 g of bamboo holocellulose powder and 60 g of DES into a glass conical bottle, stir and mix evenly with a glass rod, and heat the mixture in an oil bath at 130 °C for 120 min. After pretreatment, cool the mixture to room temperature, wash it thoroughly with deionized water, and freeze-dry the powder residue after washing;
[0059] (3) Preparation of HCNF: The powder residue after freeze-drying in step (2) was dispersed in water at a mass ratio of 1:20, and then ultrasonically disrupted to prepare bamboo holocellulose nanofibers; wherein the power of the cell disruptor used for ultrasonication was 650 W, the treatment time was 20 min, and the ultrasonication was paused for 5 s every 5 s. After the ultrasonic treatment, the sample was rapidly centrifuged to separate the supernatant and the solid residue. The supernatant finally obtained was the bamboo holocellulose nanofiber (HCNF) suspension, named CX-130.
[0060] Example 5
[0061] 1. The chemical composition of CX-100, CX-110, CX-120 and CX-130 prepared in Examples 1 to 4 was analyzed, and the results are shown in Table 1 below. After treatment with a deep eutectic solvent (DES), the cellulose component content in the lignocellulose raw material was significantly increased from the initial approximately 55% to 68%-69%, and the hemicellulose retention rate reached approximately 20%. The data results of the embodiment show that the DES system has a significant selective retention effect on the hemicellulose component, effectively avoiding the problem of excessive degradation of hemicellulose in the traditional pretreatment process. Since hemicellulose can play an interfacial reinforcement role between cellulose microfibrils, its moderate retention is conducive to improving the mechanical strength of the subsequently prepared nano-holocellulose.
[0062] Table 1 Comparison of component analysis data of nano-holocellulose prepared in Examples 1 to 4
[0063]
[0064] 2. AFM observation, crystallinity measurement and other characterizations were performed on CX-100, CX-110, CX-120 and CX-130 prepared in Examples 1 to 4. The results are as follows: Figure 1 , Figure 2 shown.
[0065] Figure 1 It is the atomic force microscope (AFM) image, Tyndall effect schematic diagram, and height distribution map of nano-holocellulose after pretreatment with a low eutectic solvent; Figure 2 The particle size distribution and zeta potential of nano-holocellulose after pretreatment with a low eutectic solvent are shown in Table 1. Figure 1 and Figure 2 It can be seen that the nanoholocellulose has a typical nanofiber morphology, is evenly dispersed, and contains a large amount of hemicellulose. Among them, the 110℃ pretreated sample (CX-110) has the smallest average height (about 2nm) and the largest average particle size distribution (about 313nm), which indicates that CX-110 has the smallest fiber diameter and the largest fiber length.
[0066] 3. Preparation of high-strength and toughness bamboo holocellulose film: The HCNF suspension prepared in Examples 1 to 4 was prepared into a nano-holocellulose suspension with a mass fraction of 1%, and a conventional Tempo oxidized cellulose nanofiber with a mass fraction of 1% was used as a control. A film was prepared by vacuum filtration, and a tensile strength test was performed using a universal tensile machine. The results are shown in FIG. Figure 3 shown.
[0067] Figure 3 It is a schematic diagram of the visible light transmittance of the nano-holocellulose film prepared in this application, a tensile stress curve of the nano-cellulose film prepared by the traditional Tempo oxidation method, a comparison chart of toughness and Young's modulus, and a comparison chart of cell activity. It can be seen that the prepared nano-holocellulose film has more significant flexibility and tensile strength than the Tempo-oxidized nano-cellulose film, and has a higher application potential. Among them, the maximum tensile stress of the prepared nano-holocellulose film reaches 112.34MPa, and the maximum toughness is 44.13 MJ / m 3 .
[0068] The results of the examples of the present application show that the thin and long fibers can play a role in transmitting the internal stress of the membrane, and the mechanical strength of the prepared nanofiber membrane is higher. However, pretreatment at too high a temperature may cause degradation of the fibers, thereby reducing the mechanical strength of the membrane.
[0069] Example 6
[0070] In order to verify the feasibility of different ratios of choline chloride / D-xylose DES in Example 1, different molar ratios of choline chloride / D-xylose were used for preparation. The selected molar ratios were choline chloride: xylose = 1:1, 1:2, 1:3, 2:1, and 3:1. Among them, 2:1 is the ratio finally selected in this application. The choline chloride / xylose mixtures under all ratios were magnetically stirred for 30 minutes under 85°C water bath heating. The results are as follows Figure 4As shown, it can be seen that only the mixture with a choline chloride / xylose molar ratio of 2:1 selected in the present application presents a clear and transparent liquid state, and DES is successfully prepared. However, the mixtures with other molar ratios present a white turbid solid-liquid mixture or an unmelted solid, and DES cannot be formed.
[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing high-strength bamboo holocellulose nanofibers, characterized in that: Firstly, a low eutectic solvent is prepared with D-xylose and choline chloride, bamboo holocellulose is treated with the low eutectic solvent, and then the solid-liquid separation is performed, the solid is dispersed, and bamboo holocellulose nanofibers are obtained by ultrasonic treatment.
2. The method for preparing high-strength bamboo holocellulose nanofibers according to claim 1, characterized in that: The molar ratio of D-xylose to choline chloride is 1:
2.
3. The method for preparing high-strength bamboo holocellulose nanofibers according to claim 1, characterized in that: The solid-liquid mass ratio of the bamboo holocellulose to the low eutectic solvent is 1g:20g.
4. The method for preparing high-strength bamboo holocellulose nanofibers according to claim 1, characterized in that: During the treatment of the bamboo holocellulose with the low eutectic solvent, a glass rod was used to stir and mix the mixture evenly, and the mixture was heated in an oil bath at 100-130° C. for 120 min.
5. The method for preparing high-strength bamboo holocellulose nanofibers according to claim 4, characterized in that: The oil bath was heated to a temperature of 110°C.
6. The method for preparing high-strength bamboo holocellulose nanofibers according to claim 1, characterized in that: The method for dispersing the solid is as follows: cooling the bamboo holocellulose residue after solid-liquid separation to room temperature, washing with deionized water and freeze-drying, and then re-dispersing the bamboo holocellulose residue in deionized water.
7. The method for preparing high-strength bamboo holocellulose nanofibers according to claim 1, characterized in that: The ultrasonic treatment method is as follows: the power of the cell disruptor used is 650W, the treatment time is 20 minutes, and the ultrasonic treatment is paused for 5 seconds every 5 seconds.
8. The method for preparing high-strength bamboo holocellulose nanofibers according to any one of claims 1 to 7, characterized in that: Here are the steps: (1) D-xylose and choline chloride were uniformly mixed in a molar ratio of 1:2 and magnetically stirred at 85°C for 30 min until a uniform transparent liquid appeared; (2) 3 g of bamboo holocellulose powder and 60 g of DES were mixed, and the mixture was heated in an oil bath at 100-130 °C for 120 min, cooled to room temperature, and thoroughly washed with deionized water. After washing, the powder residue was freeze-dried; (3) The power of the cell disruptor used was 650 W, and the processing time was 20 min. The bamboo holocellulose nanofibers were broken by ultrasonication for 5 s and then paused for 5 s, followed by rapid centrifugation to separate HCNF from solid residue.
9. The high-strength and toughness bamboo holocellulose nanofiber prepared according to any one of claims 1 to 8.
10. The use of the high-toughness bamboo holocellulose nanofibers according to claim 9 in preparing bamboo nano holocellulose films, characterized in that: The prepared bamboo holocellulose nanofibers were configured into a nano-holocellulose suspension with a mass fraction of 1%, and a film was prepared by a vacuum filtration method.
Citation Information
Patent Citations
Method for preparing bamboo heald nanocellulose in different forms by ball-milling-assisted enzyme method
CN118064520A
Preparation method of nanometer holocellulose reinforced composite membrane and prepared composite membrane
CN111944178A
Preparation method of holocellulose nanofibers
CN113322705A
Preparation method of bamboo holocellulose nanofiber with high length-diameter ratio and high hemicellulose content
CN113622051A
Method for preparing cellulose-based conductive film through combination of eutectic solvent and ultrasound
CN116410497A